The Tikhonov regularization method for the inverse source problem of time fractional heat equation in the view of ABC-fractional technique. (15th June 2021) - Djennadi, Smina; Shawagfeh, Nabil; Inc, Mustafa; Osman, M S; Gómez-Aguilar, J F; Abu Arqub, Omar
Abstract: This research considers an inverse source problem for fractional diffusion equation that containing fractional derivative with non-singular and non-local kernel, namely, Atangana-Baleanu-Caputo fractional derivative. In our study, an explicit solution set is acquired via the expansion method and the overdetermination condition at a final time. The problem is ill-posed in the meaning of Hadamard and thus the solution does not continuously depend on the input data. We have applied the Tikhonov regularization method to regularize the unstable solution. For the estimation of convergence between the exact and the regularized solutions, we focus on two parameter choice rules, a-priori and a-posteriori parameter. In the end, a simulation example is utilized and discussed to affirm the presented theoretical results.